Social Mythmaking as a Format of Structuring Reality - Yaralyan, Karine (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
The social nature of human existence implies both rational and irrational means through which the construction of reality takes place, amongst which social mythmaking plays a central role. This article, therefore, attempts to demonstrate the latter as a method of structuring existence – one that has both universal and unique socio-cultural aspects. To exemplify, the author discusses two socio-cultural and historical sections, within the framework of which social myth in the system of mass society is analyzed alongside the specificity of the mythologization of reality in the field of hyperreality. Consequently, the author concludes that despite the ontological basis of mythmaking the extreme manifestations of the latter could be detrimental in the sense that these may undermine the formal-content balance, subsequently resulting in the destruction of the entire value system of society.